Maternal & child health nursing: Care of the childbearing & childrearing family - Silbert-Flagg , JA (Brazilian Journal of Implantology and Health Sciences, 2022)
Although gestation is a physiological phenomenon and its evolution occurs in the majority of cases without intercurrences, there is a small number of pregnant women who, by particular characteristics, have presented a higher probability of unfavorable evolution, both for the fetus and for the mother, constituting the group called high-risk pregnant women (1) . In addition to the pathophysiological aspects, the literature points out the need to consider the psycho-emotional aspects when it comes to a high risk pregnancy, since the insecurities, doubts and fears can be enhanced because it is an event that puts at risk the life of the mother and the newborn(2-3). At the end of a pregnancy considered to be of high risk, the puerperium - understood as the period of the pregnancy-puerperal cycle, in which the local and systemic changes caused by pregnancy and childbirth in the woman's organism, return to the pre-gravid state(4) - is not always free of risks. Uncertainties about maternal well-being may persist after childbirth and sometimes associated with uncertainties about the child's life. Maternal health status, such as premature rupture of membranes and hypertensive diseases, has a strong association with newborns who need care in the Neonatal Intensive Care Unit (NICU)(5). Feelings such as fear of losing the child, mourning for the loss of normal pregnancy, preoccupations with the family, financial issues and work associated with the need for support in their activities of daily living are part of the daily life of this woman(6). It should be noted that in this study, the term "postpartum risk" is related to the woman who is in a risk condition related to high risk pregnancy and demands postpartum care different from usual, requiring hospitalization in a specialized care unit. When high-risk pregnancy causes the birth of a premature child who demands hospitalization, the woman experiences a spectrum of emotions ranging from boredom to anger. Feelings such as frustration, sadness, hope, irritation, impatience, guilt, fear, insecurity and anxiety are reported by them(2,6) . Therefore, the hospitalization of the puerpera at risk associated with the hospitalization of their child in the NICU can contribute to an even more challenging experience for the mother and child dyad due to physical and emotional frailty and the distancing of her child. In the midst of this adverse context, the process of construction of maternity is given away. In response to this situation, the period in which a woman physically recovers, acquires abilities to care for and read the signs of her child, strengthens the mother-child relationship, and has as a reference the way of caring for other, more experienced people, it can be potentially challenging(7). The simultaneous hospitalization of postpartum mother and postpartum child delineate a context of care with specific health needs. It is necessary to consider both the condition of the puerperal woman and her child, who demand differentiated care. Studies have explored the hospitalization of one of the components of the dyad, being incipient to address the concurrent hospitalization of mothers and their children soon after birth (6,8-10). Therefore, it is necessary to explore the situations in which mother and child demand differentiated care after childbirth and birth. It is believed that the findings may indicate the challenges they face, contributing to the qualification of professional practice and organization of health services.